The emerging story of disability associated with lymphatic filariasis: a critical review. - Lynne Michelle Zeldenryk; Marion Gray; Richard Speare; Susan Gordon; Wayne Melrose (PLoS Neglected Tropical Diseases, 2011)
Globally, 40 million people live with the chronic effects of lymphatic filariasis (LF), making it the second leading cause of disability in the world. Despite this, there is limited research into the experiences of people living with the disease. This review summarises the research on the experiences of people living with LF disability. The review highlights the widespread social stigma and oppressive psychological issues that face most people living with LF-related disability. Physical manifestations of LF make daily activities and participation in community life difficult. The findings confirm the need for the Global Programme to Eliminate Lymphatic Filariasis (GPELF) to support morbidity management activities that address the complex biopsychosocial issues that people living with LF-related disability face.